Enhancing Client-centeredness in Parkinson's Disease Care: Attending to the Psychosocial Implications of Lived Experience - Jeffrey D. Holmes PhD, OT Reg. (Ont.); Sara Lutz; Mike Ravenek; Debbie L. Rudman PhD, OT Reg. (Ont.); Andrew M. Johnson PhD (Scholarworks @ WMU, 2013)
Evidence-based practice requires that clinicians interpret the best research evidence in the context of their clinical experience, while at the same time considering client knowledge and experiences. Although clinicians are becoming increasingly skilled at the evaluation of research evidence, the evidence-based practice process often neglects client values and self-identified health issues. Ignoring these key aspects of client-centered practice may lead to interventions that fail to target the implications of a client's disease that are important to occupational participation and quality of life (QOL). A focus on client-centeredness is particularly important in progressive neurodegenerative disorders, such as Parkinson's disease, where there are no known curative treatments, and interventions must instead focus on symptom management. In this paper, we explore the published literature on the psychosocial aspects of the lived experience among individuals with Parkinson's disease, arguing that such literature provides insight into the implications of the disease and into potential treatment priorities. As such, this literature provides an additional form of evidence that raises awareness of the lived implications of this disease for clients' occupations and QOL that, in turn, may lead clinicians to be more cognizant of client values and self-identified issues.